Incidencia de la lecto-escritura en el desarrollo psicosocial de los estudiantes de 2do año de EGB de la Escuela Victoria Mosquera Mancero, cantón Montalvo, Provincia de Los Ríos - Vaca Garcia, Abdon Eduardo (2020)
The current practical document has as its theme: INCIDENCE OF READING WRITING IN THE PSYCHOSOCIAL DEVELOPMENT OF 2GB YEAR STUDENTS OF THE SCHOOL "VICTORIA MOSQUERA MANCERO" CANTÓN MONTALVO, PROVINCE OF LOS RÍOS. Subject of great impact that aims to promote understanding and the link that must exist between learning to read and learning to write, the importance that is reflected in the intellectual development of the students, the learning mechanisms involved, the external factors that influence these and probably signs that may indicate a learning problem for later and immediately implement an appropriate treatment since without it could not achieve this objective that is to solve this problem detected. Reading-writing is a communication challenge that provides appropriate tools to learn and participate in social relationships, regulate behavior and emotions from the first years of life, the present project related to the evolution and development of language and writing that It is also linked as an interrelation to a possible problem in the psychosocial and emotional aspect during the course of life, in addition to examining its repercussions with respect to prevention, mediation and training, it is said that when students have problems understanding others and To express itself, it is not surprising that this brings psychosocial problems not only in the present but also throughout his life, for this reason it is ratified that these types of inconveniences should be treated very professionally and in a timely manner